Respuesta :
Answer:
Step-by-step explanation:
-2
Apply this particular rule of logs:
log a - log b = log a/b
Therefore, log2 (3) - log2 (12) = log2 (3/12) = log2 (1/4)
This last result simplifies to log2 1 - log2 4 = 0 - 2 = -2
Answer:
-2
Step-by-step explanation:
[tex]log_2(3)-log_2(12)[/tex]
~Simplify using log properties
[tex]log_2(\frac{3}{12})[/tex]
[tex]log_2(\frac{1}{4})[/tex]
~Apply log rules
[tex]-log_2(4)[/tex]
~Rewrite
[tex]-log_2(2^2)[/tex]
~Apply log rules
[tex]-2log_2(2)[/tex]
~Apply log rules
-2 * 1
~Simplify
-2
Best of Luck!